Evaluasi Pengaruh Cedera Operator dengan Pendekatan Nordic Body Map dan Rapid Entire Body Assessment di PT. EFG - Sakiyatuddurriyah, Sakiyatuddurriyah; Ernawati, Dira (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT. EFG is an agri-food enterprise specializing in that produces quality animal protein, particularly focused on manufacturing and processing animal feed for various species. This research aims to evaluate the alleviation of symptoms related to Musculoskeletal Disorders (MSDs) among warehouse operators engaged in Manual Material Handling tasks using forklifts, with an emphasis on assessing body posture. The study's objectives include identifying the discomfort experienced by employees, analyze posture movements, and provide recommendations for action based on NBM and REBA methodologies. To address these issues, the NBM questionnaire was employed to assess the angles of worker’s body postures during their tasks. The results showed that there were 19 body parts that experienced discomfort including early indications of MSDs symptoms. The average score of the NBM questionnaire reached 55.1 which indicated a high risk so that immediate action was needed. The REBA method was used to assess body posture with a final score of 6 indicating a moderate risk and confirming the need for intervention. Operator activities are at high risk of increasing MSDs symptoms so that regular supervision of forklift use is needed, socialization regarding the importance of occupational safety and health (K3), and attention to environmental factors by adding facilities such as blowers and special forklift lanes. The recommendation from this study is the implementation of ergonomic changes that have been thoroughly evaluated.            Keywords: Body Posture, Forklift, Musculoskeletal Disorders